2008
DOI: 10.1083/jcb.200711129
|View full text |Cite
|
Sign up to set email alerts
|

p190RhoGAP is the convergence point of adhesion signals from α5β1 integrin and syndecan-4

Abstract: The fibronectin receptors α5β1 integrin and syndecan-4 cocluster in focal adhesions and coordinate cell migration by making individual contributions to the suppression of RhoA activity during matrix engagement. p190Rho–guanosine triphosphatase–activating protein (GAP) is known to inhibit RhoA during the early stages of cell spreading in an Src-dependent manner. This paper dissects the mechanisms of p190RhoGAP regulation and distinguishes the contributions of α5β1 integrin and syndecan-4. Matrix-induced tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
92
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 48 publications
6
92
0
1
Order By: Relevance
“…Cadherin-mediated adhesion inhibits Rho activation via tyrosine phosphorylation and specific localization of p190RhoGAP too (Noren et al, 2003;Wildenberg et al, 2006). p190RhoGAP is also the convergence point of adhesion signals from integrin-α5β1 and syndecan-4 in Rac activation and Rho inhibition (Bass et al, 2008) and plays a role in the caveolin-1 mediated Rac-Rho antagonism (Grande-Garcia et al, 2007). Our results presume that the role of p190RhoGAP in the Rac-Rho antagonism is not only due to its RhoGAP function as known previously but also the altered RacGAP function of p190RhoGAP.…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Cadherin-mediated adhesion inhibits Rho activation via tyrosine phosphorylation and specific localization of p190RhoGAP too (Noren et al, 2003;Wildenberg et al, 2006). p190RhoGAP is also the convergence point of adhesion signals from integrin-α5β1 and syndecan-4 in Rac activation and Rho inhibition (Bass et al, 2008) and plays a role in the caveolin-1 mediated Rac-Rho antagonism (Grande-Garcia et al, 2007). Our results presume that the role of p190RhoGAP in the Rac-Rho antagonism is not only due to its RhoGAP function as known previously but also the altered RacGAP function of p190RhoGAP.…”
supporting
confidence: 55%
“…Antagonism of Rac and Rho activity is required for several vital biological functions such as neurite outgrowth, directed cell migration or cell-cell adhesion and p190RhoGAPs seem to play a significant role in these processes (Tatsis et al, 1998;Brouns et al, 2000;Nimnual et al, 2003;Noren et al, 2003;Bradley et al, 2006;Wildenberg et al, 2006;Grande-Garcia et al, 2007;Bass et al, 2008;Bustos et al, 2008). In many cell types, Rho activity is negatively regulated by Rac via generation of ROS, which inhibits the low molecular weight protein tyrosine phosphatase (LMWPTP) ensueing tyrosine phosphorylation of p190RhoGAP (Nimnual et al, 2003).…”
mentioning
confidence: 99%
“…However, the study reported here constitutes the first evidence that αvβ3 integrin also requires cooperation with syndecan-4 to lead to FA and SF formation. This is important given that β1 and β3 reportedly have different effects on RhoA activity (Bass et al, 2008;Danen et al, 2002). Additionally, a cluster of positive charges present in Thy-1 sequence is shown here to be important in Thy-1 interaction with proteoglycans.…”
Section: Introductionmentioning
confidence: 93%
“…There is increasing evidence that Src activation and its biological functions are tightly controlled by its subcellular localization. Whereas Src at FAs inhibits Rho GTPase by inducing p190GAP activation, it activates Rho GTPase when localized to podosomes (Arthur et al, 2000;Bass et al, 2008;Berdeaux et al, 2004). In addition, the PDGF receptor uses different pools of Src to initiate distinct pathways.…”
Section: Discussionmentioning
confidence: 99%